The effects of dietary Myrtle (Myrtus communis) on skin mucus immune parameters and mRNA levels of growth, antioxidant and immune related genes in zebrafish (Danio rerio) - Roghieh Safari (2018)
© 2017 Elsevier Ltd Myrtle (Myrtus communis L., Myrtaceae) is a significant plant which naturally distributed around the globe. Although numerous studies have demonstrated the benefits of myrtle in different species, studies using the oral route are rare in the literature. In the present study, we evaluated the effect of myrtle intake on the antioxidant, immune, appetite and growth related genes as well as mucosal immune responses in zebrafish (Danio rerio) model. Zebrafish were fed control or myrtle (5, 10 and 20 g kg−1myrtle) supplemented diets for sixty days. The results showed that, oral administration of Myrtle significantly improved mucosal immune responses (the activity of lysozyme, total Ig and protease). Furthermore, fish fed 20 g kg−1showed remarkably higher antioxidant (sod and cat) enzymes gene expression compared other treatment. There were significant difference between myrtle fed fish and control group regarding tnf-alpha and lyz expression. Also, evaluation of growth (gh and igf1) related genes revealed remarkable upregulation in 20 g kg−1myrtle treatment compared other myrtle treatments and control group. Similar results was observed regarding the mRNA levels of appetite related genes (ghrl) in zebrafish fed 20 g kg−1myrtle. The present results indicated that dietary administration of myrtle improved mucosal immune parameters and altered mRNA levels of selected genes. These results on zebrafish model also highlights the potential use of Myrtle supplements as additive in human diets.